REALIZATIONS OF PROJECTION IN NEWS STORY AND EDITORIAL TEXTS - Aini Melbebahwati Saragih; Sri Minda Murni; Meisuri . . (LINGUISTIK TERAPAN, 2021)
ABSTRACTThis research deals with projection that is used in news story and editorial texts. Projection is well defined as representation of a linguistic experience in another linguistic experience. Projection is equivalent to direct and indirect or reported speech in traditional or formal grammar. As projection is an element of the logical function, it is realized as a clause complex, where there are at least two clauses. With reference to some theories, projection is also potentially realized in the form of single clause and phrase. The aim of this research is to describe similarities and differences with reference to the realizations of projection used in the news story and editorial texts. This research is conducted by using descriptive qualitative design. The data of this research are clause complexes containing projection in news story and editorial texts of Indonesian newspapers. The sources of data are taken from news story and editorial texts of four newspaper publications, namely the daily Kompas, Republika, Waspada and Sinar Indonesia Baru (SIB). The four daily newspapers are assumed to represent national and provincial or local newspapers. Each of the newspapers is represented by seven headlines for news story texts and seven leading articles for editorial texts. The data are analyzed by using interactive model in which the clause complexes are analyzed with reference to systemic functional linguistic (SFL) theory about projection. The findings indicate that there are similarities and diffrences with reference to the realizations of projetion in the news story and editorial texts of Indonesian newspapers. Keywords: Projection, News Story, Editorial, Newspaper, Systemic Functional Linguistic